Distribution and ecological risk assessment of heavy metals in roadside soil along the Hemat Highway of Tehran, Iran - Movafagh, Afsaneh; Mansouri, Nabiollah; Moattar, Faramarz; Vafaeinejad, Ali Reza (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The impact of land use and a distance from the highway on heavy metal concentration in soils along the highway has been investigated. 28 soil samples were collected in August 2014 from the roadside soils of the Hemmat highway of Tehran, Iran. The results showed that the mean concentrations of Pb, Cr, Ni, Zn and Cd were 144, 17.20, 18.91, 86.84, 3.86 mg/kg–1, respectively. With exception for Cd, the concentrations of the heavy metals decreased upon increasing distance from the highway that shows the background amount of cadmium in the soil area was high. The values of the enrichmentfactor (EF) showed that Ni, Zn and Cr have a natural source (EF < 10) and Pb and Cd have an anthropogenic source (EF > 10). The anthropogenic sources are emphasized for these heavy metals, thus indicating the strong human influence. The mean values of geoaccumulation index (Igeo) for Pb, Zn, Cd were high at residential, under-construction and green space land uses. The ecological risk index (RI) for roadside soils was higher than 3 indicating that sampling sites had a considerable ecological risk. The potential ecological risk index for single metal decreases in the following sequence: Cd > Pb > Ni > Zn > Cr.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 5-17
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma